Chaetocin Abrogates the Self-Renewal of Bladder Cancer Stem Cells via the Suppression of the KMT1A–GATA3–STAT3 Circuit - Yang, Zhao; Wang, Haifeng; Zhang, Nan; Xing, Tianying; Zhang, Wei; Wang, Guoqing; Li, Chong; Yu, Changyuan (Frontiers in Cell and Developmental Biology, 2020)
Bladder cancer stem cells (BCSCs) have the abilities of self-renewal, differentiation, and metastasis; confer drug resistance; and exhibit high tumorigenicity. We previously identified that the KMT1A–GATA3–STAT3 axis drives the self-renewal of BCSCs. However, the therapeutic effect of targeting KMT1A in BCSCs remains unknown. In this study, we confirmed that the expression of KMT1A was remarkably higher in BCSCs (3–5-fold) than those in bladder cancer non-stem cells or normal bladder epithelial cells. Among the six KMT1A inhibitors, chaetocin significantly suppressed the cell propagation (inhibition ratio: 65%–88%, IC50 = 24.4–32.5 nM), induced apoptosis (2–5-fold), and caused G1 phase cell cycle arrest (68.9 vs 55.5%) of bladder cancer (BC) cells, without influencing normal bladder epithelial cells. More importantly, chaetocin abrogated the self-renewal of BCSCs (inhibition ratio: 80.1%) via the suppression of the KMT1A–GATA3–STAT3 circuit and other stemness-related pathways. Finally, intravesical instillation of chaetocin remarkably inhibited the growth of xenograft tumors (inhibition ratio: 71–82%) and prolonged the survival of tumor-bearing mice (70 vs 53 days). In sum, chaetocin abrogated the stemness maintenance and tumor growth of BCSCs via the suppression of the KMT1A–GATA3–STAT3 circuit. Chaetocin is an effective inhibitor targeting KMT1A in BCSCs and could be a promising therapeutic strategy for BC.